Persepsi Siswa Generasi Z terhadap Pengaruh Media Sosial dalam Perilaku Akademik dan Konsentrasi Belajar Siswa di Jenjang Sekolah Dasar (SD) - Yulia Rahmawati; Nabilah Nabilah; Yusmandita Nafa Lutfiah; Athifah Muzharifah; Mochamad Iskarim (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
Social media has become an integral part of Generation Z's life, including elementary school students, who are known as the tech-savvy generation. This study aims to examine Generation Z students' perceptions of the influence of social media on their academic behavior and learning concentration through a literature study approach. Data were collected from various current literature sources and analyzed using thematic analysis methods. The results of the study indicate that social media has a dual impact: platforms such as YouTube and educational applications such as Kahoot increase motivation and access to learning resources, but uncontrolled use causes distraction, procrastination, and decreased learning concentration. The characteristics of Generation Z, such as dependence on technology and the need for digital existence, strengthen the influence of social media on their academic behavior. Therefore, a balanced educational approach is needed to maximize the benefits of social media while minimizing its negative impacts. This study provides insight for educators and parents in managing the use of social media wisely.